A new species of the genus Micropeza Meigen (Diptera: Micropezidae) from Brazil - Harterreiten-Souza, Érica Sevilha; Sujii, Edison Ryoiti; Pujol-Luz, José Roberto (Zootaxa, 2014)
The stilt-legged fly genus Micropeza contains 82 valid species. Currently 10 species are recorded in Brazil. Here we describe a new species, M. dactyloptera sp. nov., based on 108 specimens (55 males and 53 females) from the States of Goiás, Paraná, and Distrito Federal, Brazil.